Marine Actinobacteria a New Source of Antibacterial Metabolites to Treat Acne Vulgaris Disease-A Systematic Literature Review - Maria Clara De La Hoz-Romo; Luis Díaz; Luisa Villamil (MDPI AG, 2022)
Acne vulgaris is a multifactorial disease that remains under-explored; up to date it is known that the bacterium Cutibacterium acnes is involved in the disease occurrence, also associated with a microbial dysbiosis. Antibiotics have become a mainstay treatment generating the emergence of antibiotic-resistant bacteria. In addition, there are some reported side effects of alternative treatments, which indicate the need to investigate a different therapeutic approach. Natural products continue to be an excellent option, especially those extracted from actinobacteria, which represent a prominent source of metabolites with a wide range of biological activities, particularly the marine actinobacteria, which have been less studied than their terrestrial counterparts. Therefore, this systematic review aimed to identify and evaluate the potential anti-infective activity of metabolites isolated from marine actinobacteria strains against bacteria related to the development of acne vulgaris disease. It was found that there is a variety of compounds with anti-infective activity against Staphylococcus aureus and Staphylococcus epidermidis, bacteria closely related to acne vulgaris development; nevertheless, there is no report of a compound with antibacterial activity or quorum-sensing inhibition toward C. acnes, which is a surprising result. Since two of the most widely used antibiotics for the treatment of acne targeting C. acnes were obtained from actinobacteria of the genus Streptomyces, this demonstrates a great opportunity to pursue further studies in this field, considering the potential of marine actinobacteria to produce new anti-infective compounds.